O uso de resina composta bulk-fill realmente diminui o tempo clínico em restaurações de dentes posteriores? - Bellinaso, Mariana Dantas (2018)
This study aimed to systematically review the literature to compare the time required for filling cavities (restorative clinical time) in posterior teeth using a bulk-fill and conventional (layering technique) resin composite. A search for clinical trials and in vitro studies was performed in PubMed/MEDLINE, Scopus, LILACS, BBO, Cochrane Library, Clinical Trials and ReBEC databases. No publication year or language restriction was considered. From 623 potentially eligible studies, 125 were selected for full-text analysis, 4 were included in the systematic review and 3 in the meta-analysis. Two authors independently selected the studies, extracted the data and assessed the risk of bias. Mean difference was calculated for the clinical time means from bulk-fill resin composite and conventional resin composite. Statistical analysis was performed using RevMan5.3, with random effects model, at a significance level of p 0.05. Overall, the restorative clinical time was lower when bulk-fill resin composites were used (p=0.01) than conventional resins, solely when full-body bulkfill resin composites were evaluated (p<0.01). There was no difference between flowable bulk-fill resins and conventional ones (p=0.08). Moderate to substantial heterogeneity were detected. The use a full-body bulk-fill resin composites require shorter time to perform restorations in posterior teeth than conventional resins placed incrementally. There is not enough evidence to draw the same conclusion regarding flowable bulk-fill resin composites.